Real Power of the perspective based on Human Relations and Behavioral Styles - Paredes-Riera, Julio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2016)
The breakdown of the traditional paradigms in the Ecuadorian education emerges to the urgent need for the omnipresence of the knowledge society, the requirements of solution are varied ,the effectiveness mitigated by context, not a panacea this proposal has legitimized the efficiency and effectiveness of academic training process of versatile professionals, competent and competitive contributing to sustainable, sustainable development of the country in line with its regional peers focused on international competitiveness (professional climbing). The skills of the students are identified, their skills are power, meets their personal needs, and it contributes to meeting the needs of the collective permeating warm human relationships, maximizing cooperative behavior assertive achievements through actual factual evidence. Methods, techniques and strategies vary according to the level that present the pre-professional; a standard educational model based on real skills, communication and satisfaction of human needs in accordance with the ecosystem, legitimizes the formation processes in real scenarios through cooperation.